The Proportion of Cognitive Aspects of Question in Mathematics Textbook Based on Marzano's Taxonomy: An Indonesian Case in Implementing New Curriculum - Dhila Ardiani Rasyidi; Widodo Winarso (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
Mathematical textbooks are one source of learning that has an important role in learning activities. But the existence of the government-issued mathematics textbook (BSE) which is currently widely used in class X high schools, still does not know the quality of its cognitive aspects. The purpose of this study was to find out the questions contained in class X high school mathematics textbooks had met the criteria of a good question according to the Marzano cognitive aspects. Qualitative descriptive research was used to analyze competency test questions in mathematics books. Data was collected through a question categorization checklist based on Marzano's cognitive aspects validated by experts. Guidelines for question analysis based on Marzano's taxonomy's cognitive aspects consisted of levels of cognitive retrieval, levels of cognitive understanding, levels of cognitive analysis, and levels of cognitive knowledge. The results showed that the percentage of question distribution for the recall rate was 17%, at an understanding level of 14%, 30% analysis level, and 39% knowledge level; in other words, cognitive distribution in high school mathematics class X textbooks was still not ideal according to proportional allocation of aspects cognitiveÂ Â